2006
DOI: 10.3748/wjg.v12.i8.1281
|View full text |Cite
|
Sign up to set email alerts
|

Clinical correlation of gallstone disease in a Chinese population in Taiwan: Experience at Cheng Hsin General Hospital

Abstract: INTRODUCTIONGallstone disease (GSD) is one of the most common diseases in developed countries. Recent studies indicate varying prevalence of GSD with several predisposing factors in different study populations [1][2][3][4][5][6][7][8][9] . From a medical economic perspective, the direct and indirect costs of treating GSD patients were estimated at $16 billion and account for more than 800 000 hospitalizations yearly in the United States [9,10] . In Taiwan, the prevalence of GSD in the general population was 4.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
55
0
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(63 citation statements)
references
References 23 publications
6
55
0
2
Order By: Relevance
“…11,27,28 Among patients with chronic hepatitis, fructose load may cause a substantial increase in serum uric acid levels. 5,7 Furthermore, serum uric acid levels are high in patients with chronic liver lesions. Our results regarding the significant association between high serum ALT level and hyperuricemia are similar to those reported in other studies.…”
Section: 11-14mentioning
confidence: 99%
“…11,27,28 Among patients with chronic hepatitis, fructose load may cause a substantial increase in serum uric acid levels. 5,7 Furthermore, serum uric acid levels are high in patients with chronic liver lesions. Our results regarding the significant association between high serum ALT level and hyperuricemia are similar to those reported in other studies.…”
Section: 11-14mentioning
confidence: 99%
“…Women (3.0%) exhibited a significantly higher prevalence of multiple stones than did men (1.7%) (P = 0.04). Participants aged 50 years and older (96/918 = 10.5%) had a 5-fold risk for prevalent GSD compared with those aged 50 years and younger (30/1468 = 2.0%) [12].…”
Section: Basic Epidemiology Of Gallstone Disease Screeningmentioning
confidence: 97%
“…A pilot study was performed using the data of 100 randomly selected healthy participants; none of our patients were included in this stage. The κ value of the interobserver reliability for the diagnosis of GSD among the medical specialists was 0.79 (95%CI: 0.610.95) [10] .…”
Section: Diagnosis Of Gsdmentioning
confidence: 98%
“…Gallbladder polyps were not included. The study cases were identified among all types of GSD patients [10] . To determine consistent criteria for the diagnosis of GSD, the κ statistic was further used to evaluate the interobserver reliability among various medical specialists.…”
Section: Diagnosis Of Gsdmentioning
confidence: 99%